2023
DOI: 10.3390/foods12152965
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Acidophilic Lactic Acid Bacteria on Food and Human Health: A Review of the Current Knowledge

Mehmet Arif Icer,
Sena Özbay,
Duygu Ağagündüz
et al.

Abstract: The need to improve the safety/quality of food and the health of the hosts has resulted in increasing worldwide interest in acidophilic lactic acid bacteria (LAB) for the food, livestock as well as health industries. In addition to the use of acidophilic LAB with probiotic potential for food fermentation and preservation, their application in the natural disposal of acidic wastes polluting the environment is also being investigated. Considering this new benefit that has been assigned to probiotic microorganism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 165 publications
1
6
0
Order By: Relevance
“…The best growth pHs for all the isolates fell between 5.0 and 6.0. Mehmet et al (2023) stated that while most LAB grow best at pH levels close to neutral, some bacterial species, including Lactobacillus, which is one of the isolates used in this study, are different and grow well at pH 3 and this is reflective of our results in this study. Song et al (2021), also reported the tolerance of Pediococcus pentasaceus and Pediococcus acidilactic at pH values from 2.5 to 4.…”
Section: Effect Of Temperature On the Growth Of Bacterial Isolatessupporting
confidence: 57%
“…The best growth pHs for all the isolates fell between 5.0 and 6.0. Mehmet et al (2023) stated that while most LAB grow best at pH levels close to neutral, some bacterial species, including Lactobacillus, which is one of the isolates used in this study, are different and grow well at pH 3 and this is reflective of our results in this study. Song et al (2021), also reported the tolerance of Pediococcus pentasaceus and Pediococcus acidilactic at pH values from 2.5 to 4.…”
Section: Effect Of Temperature On the Growth Of Bacterial Isolatessupporting
confidence: 57%
“…L. acidophilus is a well-known probiotic that is beneficial for gut health [ 59 ]; incorporating it into fermented BP can add probiotic properties to the final product, making it more beneficial for consumption. It is effective in producing lactic acid, which can help in preserving the BP and maintaining a stable pH during fermentation [ 25 ]. A. kunkeei is commonly found in bee products and is well adapted to the bee environment [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus plantarum , with its robust fermentative ability and adaptability to different substrates, has been documented to improve the digestibility and nutritional profile of various foods. The fermentation process with L. plantarum and L. acidophilus not only breaks down complex food matrices but also potentially increases the levels of essential amino acids, vitamins, and bioactive peptides, adding to the functional value of BP [ 21 , 22 , 23 , 24 , 25 ]. One of the notable benefits of L. plantarum in fermentation is its capacity to improve the bioavailability of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5]. Most of the functional foodstuffs are produced by species and (or) strains belonging to lactic acid bacteria (LAB), which are generally recognized as safe (GRAS) and confer a multitude of functional and sensory properties [6,7]. In this regard, for outside plant-based fermented foods or drinks which are currently widely studied, the LAB starter cultures are directed towards the fermentation of novel substrates from plant foods, herbs, or spices in order to improve their health-promoting effects by stimulating the release or production of bioactive metabolites [8][9][10].…”
Section: Introductionmentioning
confidence: 99%